TEACHING-LEARNING CHALLENGES IN THE PANDEMIC IN THE EARLY YEARS OF ELEMENTARY SCHOOL - Cristina da Silva, Isabel; Natália da Silva Alcântara, Francisca (Revista Gênero e Interdisciplinaridade, 2024)
The objective of this article was to analyze through the literature review the difficulties encountered during the pandemic in teaching and learning in the early years of elementary school. The research is a bibliographic review of a qualitative nature. It was carried out in the databases: Scientific Electronic Library Online (SCIELO) Capes and government portals. The criteria used for data collection were inclusion, periods or publications that approach: education as an essential right for children, the importance of the school community in the epidemiological crisis scenario and the teaching strategies used to overcome the crisis moment in Brazil. And the exclusion criteria: content not relevant to the theme, publications in a foreign language, incomplete or not referenced. It was found that there are many and varied challenges faced by students, the family, especially for teachers in emergency remote teaching. The strategies used by educators, despite the limitations, were imposed for the growth of students in the early years of elementary school. While the family also helped in this learning process, amid difficulties such as lack of resources to have access to technologies and lack of preparation in monitoring school activities, they made an effort to follow the teacher's guidelines in order to continue. the education of their children. Therefore, it was observed that teachers must be properly qualified to use digital communication technologies. Remote teaching during the pandemic brought together students, teachers and families through digital platforms, making it clear, the importance of this bond in the emotional, cultural and social development of the child as a critical and active being in society.